Comparison of Propofol and Ketamine Combination (Ketofol) and Propofol and Fentanyl Combination (Fenofol) on Quality of Sedation and Analgesia in the Lumpectomy: A Randomized Clinical Trial - Nazemroaya, Behzad (Adv Biomed Res, 2018)
BACKGROUND: Breast lumpectomy is an integral part of the treatment of mammary masses in women. This study was conducted to evaluate and compare two-drug combinations of propofol–ketamine (PK) (ketofol) and propofol–fentanyl (PF) (fenofol) on quality of sedation and analgesia in lumpectomy. MATERIALS AND METHODS: This was a randomized, double-blind, clinical trial performed on 64 patients aged 15–70 years with breast cancer lumpectomy referred to Isfahan's Seyed Al-Shohada Hospital. Consequently, patients were divided into two groups of 32 patients, each group receiving PF combination or PK combination during anesthesia. RESULTS: The patients in two groups, PF and PK, were compared in their sedation levels, severity of pain, and other variables. The mean arterial blood pressure, systolic blood pressure, and heart rate (HR) did not show any significant difference at the beginning of the study in the two groups, but the fenofol (PF) group had a significantly lower oxygen saturation than the ketofol (PK) group. The sedation level was significantly lower in the fenofol group than the ketofol group (P < 0.001). The mean pain intensity was significantly lower in the PF group than the PK group (P < 0.001). CONCLUSION: The two combinations of ketofol and fenofol cause rapid, favorable, safe anesthetic with minimal side effects and hemodynamic effects but it may be a superior alternative to fenofol combination, in terms of respiratory depression.